ANALISIS KEMASAN DAN MEREK TERHADAP KEPUASAN KONSUMEN MELALUI UJI ORGANOLEPTIK HASIL PANELIS SAMPEL DI BAGIAN QUALITY CONTROL PADA PRODUK BISKUIT ROMA PT. MAYORA INDAH TBK, TANGERANG - AR. Chaerudin AR. Chaerudin (NIAGARA Scientific Journal, 2018)
Along with the development of the era of globalization is increasingly advanced, thus causing consumers to be more selective in determining the quality of products provided to achieve customer satisfaction, the company is required to continue to develop and improve product quality in order to compete in an increasingly competitive business world, Research Objectives It intends to know the results of packaging analysis and Brand on customer satisfaction of biscuit products of Roma PT. Mayora Indah Tbk, Tangerang, This research method uses a qualitative approach with case study method, this method aims to explain and understand in particular facts or characteristics of a particular population or a particular field factually and accurately in the analysis of the influence of packaging and brand Biscuit Roma products PT. Mayora Indah Tbk. Tangerine to customer satisfaction The results of the research analysis obtained from organoleptic testing at PT. Mayora Indah Tbk, in analyzing the results of organoleptic testing of packaging and brand on consumer satisfaction, packaging and brands entered in to the maximum standard in organoleptic testing, so it can be concluded that packaging and brand play a very positive role consumer satisfaction biscuit products roma.